An investigation into syntactic and lexical interlingual errors in spoken english committed by the first year students at the college of fpt polytechnic in danang - Trương,Thị Hoàng Phúc (ĐHĐN., 2015)
This paper is based on an error analysis of the English spoken work of the first year students at the College of FPT Polytechnic in Danang who could be described as ESL false beginners. The source of the data consists of one hundred and twenty English conversations made by the participants about the assigned topics in the English school syllabus, which were then transcribed into written form. The purpose of the study is to identify the syntactic and lexical intelingual errors and to find out the types and the frequency of occurrence in the students’ spoken work. The syntactic and lexical errors collected are identified and classified using Politzer and Ramirez’s (1973) Linguistic Category Taxonomy and James’s (1998) Lexical Error Taxonomy repectively as guidelines. To categorize the interlingual errors, the study employed the Classification of Interlingual Errors proposed by Lott (1983) and Alonso (2007); accordingly these errors detected were classified into four types: Overextension of Analogy, Transfer of Structure, Interlingual/ Intralingual error and Substitution. The findings presented the types of syntactic and lexical interlingual errors, their detailed description, and the frequency of occurrence of each error type. With respect to syntactic interlingual errors, the most commonly occurring type is constituted by the group Interlingual/Intralingual errors while the group Transfer of Structure errors formed the second most frequent group. As far as lexical interlingual errors are concerned, the most common type of Interlingual errors is the group Transfer of structure, the second main type of lexical interlingual error is Overextension of Analoly. It is hoped that this sudy would give a new perspective in the beginning learners’ syntactic and lexical interlingual errors, and provide data for teachers and syllabus designers in an attempts to minimize students’ syntactic and lexical interlingual errors.